Penerapan Suctioning Terhadap Perubahan Saturasi Oksigen Pasien Gagal Nafas Yang Terpasang Ventilator Di ICU RSI PKU Muhammadiyah Pekajangan - Kartikasari, Dian; Mas'ut, Ibnu (Universitas Malahayati, 2024)
ABSTRACT Patients with respiratory failure require intensive care and are a significant cause of morbidity and mortality. Respiratory failure is a significant gas exchange capacity failure in the respiratory system, where a person is unable to effectively cough due to excessive secretions causing airway obstruction. This can be managed with suctioning to clear the airway, reduce secretion buildup, and prevent lung infections. According to the World Health Organization (WHO), the prevalence of critical patients in Intensive Care Units (ICU) increases annually, with a mortality rate of 1.1 to 7.4 million people due to critical illnesses. In Asia, 1,285 patients were placed on mechanical ventilation with an Endotracheal Tube (ETT) in 16 hospitals, including Indonesia. A study conducted at RSUD DR. Wahidin Sudirohusodo Makassar in 2019 showed 241 patients with ETT. Another study at RSUD dr. Soediran Mangun Sumarso Wonogiri in 2015 had 105 ICU patients, while ICU RSI PKU Muhammadiyah Pekajangan had 88 ventilated respiratory failure cases in 2022, increasing to 189 cases in 2023, prompting the application of